Evaluating healing pattern after fibrotomy and myotomy followed by grafting with buccal fat pad and collagen in oral submucous fibrosis patients: a case series - Dwivedi, Ajita; Tiwari, Abhishek M.; Kumar, Abhigyan (International Surgery Journal, 2021)
This study was conducted to assess the healing pattern of buccal fat pad and collagen as intraoral graft post fibrotomy and masticator myotomy in oral submucous fibrosis patients. The study was conducted on 20 patients with reduced mouth opening due to oral submucous fibrosis (Khanna and Andrade classification grade 3 and 4 a), randomly divided into 2 groups. In one group, buccal fat pad was harvested and in other group only wet bovine collagen sheet was applied as surgical dressing in the intra-oral wound after fibrotomy and masticator myotomy. Healing pattern of both as graft material were compared based on clinical findings. Healing occurs following epithelialization of the buccal fat pad which gradually takes the color of the buccal mucosa. Xenogenic collagen offers better coverage of the surgical wound but degenerates itself in the course of healing. The covered wound epithelializes without scar tissue formation and patients experience less symptoms during healing phase.